Annual Agriculture Nutrition and Health Academy Week strengthens interdisciplinary research capacity among individuals from low- and middle-income research institutions - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
The Agriculture, Nutrition and Health Academy Week has helped convene a global community of researchers and research users working on agriculture, nutrition, and health challenges. Since 2016, A4NH have co-organized this annual event with the London School of Hygiene and Tropical Medicine (LSHTM). These events have enhanced individual capacity of early career researchers from low- and middle-income countries in terms of research involvement and skills and filled a gap in networking and mutual learning opportunities around agriculture, nutrition, and health